When breast cancer patients participate in ritual interactive activities: the mechanism of perceived emotional synchrony on health information avoidance - Jie Chen; Jie Chen; Yang Yang; Fangjuan Du; Jie Li (Frontiers in Psychology)
IntroductionHealth information avoidance (HIA) creates serious health risks, particularly for patients with serious health problems such as breast cancer. Although existing research has explained how emotional responses affect HIA from several perspectives, little attention has been paid to how perceived emotional synchrony (PES), as an antecedent, influences HIA behavior, especially in the context of breast cancer patients participating in ritualistic interactive activities. In this study, we constructed a moderated chain mediation model drawn on the Interactive Ritual Chains (IRCs) theory, combined with social cognitive theory to test the relationship between PES and HIA behaviors in cancer patients. At the same time, the important individual characteristic of cancer staging has been overlooked in studies of boundary mechanisms in HIA. We further explored the moderating role of cancer staging.MethodsWe assembled a sample of 302 female patients with breast cancer who participated in ritual interaction activities in five Grade A tertiary hospitals in China. In this study, regression analysis was conducted using SPSS 23.0 and MPlus 8.3 to explore the relationship between PES, positive emotions, coping self-efficacy, and HIA variables to test the hypotheses.ResultsEmpirical analyses revealed that PES was negatively correlated with HIA in the context of breast cancer patients participating in ritual interaction activities. Additionally, positive emotions and coping self-efficacy acted as mediators between PES and HIA. Furthermore, positive emotions and coping self-efficacy played a chain-mediation role in the relationship between PES and HIA during ritual interaction activities. Disease stage significantly moderated the strength of these chain-mediated effects, with the chain-mediated influence of positive emotions and coping self-efficacy between PES and HIA being significantly stronger in patients with advanced breast cancer.DiscussionThe study constructed a quantitative conceptual model of how PES influences HIA in cancer patients. Cancer staging was shown to have a moderating effect on this mechanism, which enriches theoretical explanations of HIA behavior. In practice, promoting PES through structured ritual interactions can strengthen emotional connections among breast cancer patients. Developing stage-specific support strategies may facilitate more personalized interventions. Future research should examine the multilevel mechanisms of ritual interaction and the situational role of HIA.